"Apprendre à vaincre en le regardant faire". Lo que Gibbon aprendió de Justo Lipsio - Ballesteros Sánchez, Juan Ramón (2022)
Justo Lipsio publicó en 1598 la primera ed. de Admiranda sive de magnitudine romana libri IV, una de las fuentes bibliográficas del Decline and Fall de Gibbon. El trabajo presenta las relaciones entre ambos proyectos historiográficos y revisa el análisis que de esa relación realizó J. G. A. Pococken Barbarism and Religion. Volume Three. The First Decline and Fall (2003).
Iustus Lipsius published in 1598 the first ed. of Admirandasive de magnitudine romana libri IV, one of the bibliographical sources for Gibbon's Decline and Fall. The article presents the relationship between both historiographical projects and reviews the analysis of that relationship made by J. G. A. Pocock in Barbarism and Religion. Volume Three. The First Decline and Fall (2003).
Keywords: Lipsius, Justus, -- 1547-1606; Historiografía